Kemampuan Berpikir Kreatif Matematika Materi Kubus Dan Balok Siswa MTsN 1 Makassar - Mutmainah - Mutmainah (Program Studi Pendidikan Matematika, 2021)
This study aims to reveal students' mathematical creative thinking skills which include indicators of fluency, flexibility, and originality by describing students' answers in solving cube and block problems. This research was conducted on the superior grade VIII students of MTsN 1 Makassar, totaling 39 students. The research subjects were taken as many as 6 people using the criteria for high, medium, and low group levels, every 2 students at each level. The instrument used is a creative thinking ability test, which consists of 4 items of description with qualitative descriptive analysis. The results showed that the students' mathematical creative thinking skills including the three indicators were very good based on the percentage value of each indicator being above 50%. In the fluency indicator, the percentage value is 100% for item number 1 and 95.83% for question number 2, the percentage value of the flexibility indicator for item number 2 and 4 is 95.83% and 91.67%, respectively, and the percentage value of the novelty indicator is questions number 2 and 4 are 75% and 70.83%, respectively. From the three indicators above, the percentage value of students' creative thinking ability is low when compared to the other two indicators, this shows that students are less able to produce unusual answers/ideas and the suitability of the answers given is very irrelevant to the problem.